Apakah Leverage, Ukuran Perusahaan dan Masa Jabatan Direksi Mempengaruhi Kualitas Laporan Keuangan Bank Umum Syariah? - Indriyana Puspitosari (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2019)
financial statements have an important role for stakeholders to be able to provide information for decision making. Therefore, managers are required to be able to prepare quality financial reports. Financial statements are declared qualified if they meet the qualitative quality of financial statements. In this study trying to show the effect of leverage, firm size and tenure of directors on the quality of financial statements. The object of this study is in Islamic banks in Indonesia. The research sample consisted of 11 Islamic commercial banks with an observation period in 2013-2017. From the results of data processing, the results show that the leverage variable cannot affect the quality of islamic banks financial statements, while firm size and director tenure have a significant effect on the quality of financial statements